Participação em atividade física e comportamentos de risco à saúde em adolescentes: diferenças entre sexos - Nicolau Augusto Malta; Gabriela Cansian Martins; Michael Pereira Da Silva; Edmar Roberto Fantinelli; Jhonatan Gritten Campos; Wagner De Campos (Universidade Estadual do Oeste do Paraná, 2016)
The aim of this study was to verify the existence of significant differences in levels of physical activity, sedentary habits and consumption of tobacco and alcohol among boys and girls. The sample consisted of 815 adolescents from 11.0 to 15.9 years (409 boys and 406 girls) enrolled in public schools in the city of Curitiba, State of Parana. To assess the level of physical activity (PA) was used questionnaire Youth Activity Profile. For the evaluation of time spent in sedentary activities was used Sedentary Activities Questionnaire for Adolescents. For the identification of cigarette and alcohol consumption were version of the questions used in the Brazilian version of the Youth Risk Behavior Survey (YRBS). Descriptive analysis was used to characterize the sample. For comparisons, we used the Mann-Whitney U test for comparison between groups for the scores of physical activity and sedentary time, the chi-square test for cigarette and alcohol consumption, adopting p<0.05. The mean age was 14±2.5 years for boys and 13.74±2.1 for girls. Boys had higher scores of AF in school (2.6 vs 2.1, p=0.000), AF at home (2.3 vs 2.0, p=0.000), AF at the weekend (2.5 vs 2.5, p=0.000) and total physical activity (2.3 vs 1.8, p=0.000). Of teens who reported having drunk at least one day in the last 30 days, 55.7% were female and 44.3% were boys. Other variables were not significant when compared between the sexes. The boys were more active than girls in all analyzed environments and also in the overall AF. In the case of girls, they were more susceptible to alcohol consumption when compared to their male counterparts. The variables sedentary behavior and cigarette smoking were not significant.